Determinants of Consumer Adoption of Online Air Ticketing in Nepal - Pant, Kaushiki; Karki, Manisha Kumari; Gyawali, Safal; Pathak, Srijana; Pradhan, Sumit (Nepalese Journal of Economics, 2024)
This study examines the determinants of consumer adoption of online air ticketing in Nepal. Consumer adoption is the dependent variable. The independent variables are price, promotion, service quality, brand name, trust and experience. The primary source of data is used to assess the opinions of respondents regarding consumer adoption of online air ticketing in Nepal. The study is based on 103 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The multiple regression models are estimated to test the relationship and importance of different variables on consumer adoption of online air ticketing in Nepal. The result shows that price has a positive impact on consumer adoption of online air ticketing. It indicates that fair price of the airline ticket leads to increase in consumer adoption of online air ticketing. Likewise, promotion has a positive impact on consumer adoption of online air ticketing. It indicates that better promotional strategies encourage the customers to buy the tickets of the particular airline company. Similarly, there is a positive impact of trust on consumer adoption of online air ticketing. It indicates that high level of trust drives the customer to purchase airline tickets. Similarly, brand name has a positive impact on consumer adoption of online air ticketing. It indicates that renowned brand name of the airline stimulates the ticket purchasing behavior of the customers. Furthermore, experience has a positive impact on consumer adoption of online air ticketing. It resembles that good experience of the particular airline company leads to consumer adoption of online air ticketing.